Notes on Kaszabjbaloghia with the description of a new species from Ecuador (Acari: Mesostigmata: Uropodidae) - Jenõ Kontschán (Zoologia (Curitiba), 2010)
Kaszabjbaloghia Hirschmann, 1973, distributed in South-America, is characterized by the following combination of characters: reduced marginal shield, posteromarginal setae placed on membranous cuticle on the dorsal idiosoma, linguliform genital shield in females, oval or egg-like genital shield bearing one pair needle-like setae in males, and the characteristic shape of peritremes. In this contribution, I provide short redescriptions of the known species of Kaszabjbaloghia and describe a new species, K. ecuadorica sp. nov., from Ecuador. The new species is similar to K. kaszabi Hirschmann, 1973, but differs from the latter in the ornamentation of genital shield of the female and the number of sternal cavities. Additionally, we transfer K. hirschmanni Hiramatsu, 1978 to Hutufeideria Hirschmann & Hirmatsu, 1977 (as Hutufeideria hirschmanni (Hiramatsu, 1978) comb. nov.) on the basis of the following: setation of dorsal shield, ornamentation of caudal part of the dorsal shield, shape of hypostomal setae, shape of internal malae and setation of the palp. An identification key to the species of Kaszabjbaloghia is also provided. Original illustrations and scanning micrographs are provided for all species.